Effects of Mixed Baculovirus Infections in Biological Control: A Comprehensive Historical and Technical Analysis - Ferrelli, María Leticia; Salvador, Ricardo (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Baculoviruses are insect-specific DNA viruses that have been exploited as bioinsecticides for the control of agricultural and forest pests around the world. Mixed infections with two different baculoviruses have been found in nature, infecting the same host. They have been studied to understand the biology of virus interactions, their effects on susceptible insects, and their insecticidal implications. In this work, we summarize and analyze the in vivo baculovirus co-infections reported in the literature, mainly focusing on pest biocontrol applications. We discuss the most common terms used to describe the effects of mixed infections, such as synergism, neutralism, and antagonism, and how to determine them based on host mortality. Frequently, baculovirus co-infections found in nature are caused by a combination of a nucleopolyhedrovirus and a granulovirus. Studies performed with mixed infections indicated that viral dose, larval stage, or the presence of synergistic factors in baculovirus occlusion bodies are important for the type of virus interaction. We also enumerate and discuss technical aspects to take into account in studies on mixed infections, such as statistical procedures, quantification of viral inocula, the selection of instars, and molecular methodologies for an appropriate analysis of baculovirus interaction. Several experimental infections using two different baculoviruses demonstrated increased viral mortality or a synergistic effect on the target larvae compared to single infections. This can be exploited to improve the baculovirus-killing properties of commercial formulations. In this work, we offer a current overview of baculovirus interactions in vivo and discuss their potential applications in pest control strategies.